IN-VIVO ANTI-DIARRHOEAL ACTIVITY AND PHYTOCHEMICAL SCREENING OF ETHANOL STEM BARK EXTRACT OF VITELLARIA PARADOXA GAERTN F. (SAPOTACEAE) - Abdullahi, Z.; Jimoh, A. A.; Patrick , B. E.; Yakubu, M. I.; Mallam, D. (FUDMA JOURNAL OF SCIENCES, 2020)
Different parts of Vitellaria paradoxa plant have many applications in ethno-medicine. Some of the uses of this plant include treatment of diarrhoea and other GIT disorders. In this study the antidiarrhoeal activity of the ethanol extract of Vitellaria paradoxa was evaluated using three experimental models: Castor oil-induced diarrhoea; small intestinal motility and intestinal fluid accumulation (enteropooling) models in mice. Five groups of five mice were used for each model. Group one mice received 10 ml/kg of distilled water, while groups 2, 3, and 4 received 125, 250 and 500 mg/kg of the extract orally respectively. Group 5 mice received Loperamide 5 mg/kg orally. Oral median lethal dose (LD50) of the extract was determined using OECD (2008) Guideline 425. Phytochemical studies were conducted using standard procedures. The LD50 was estimated to be greater than 5000 mg/kg body weight and there were no signs of mortality or visible signs of toxicity in all the mice treated. Phytochemical screening revealed the presence of carbohydrates, alkaloids, flavonoids, saponins, tannins, triterpenes, steroids, cardiac glycosides and anthraquinones glycosides. Extract showed a dose-dependent anti-diarrhoeal activity by reducing stool frequency and consistency. The extract at the higher doses significantly (p < 0.05) inhibited GIT motility and castor oil-induced enteropooling, comparable to that of the reference control drug Loperamide. The study showed that ethanol stem bark extract of Vitellaria paradoxa possess anti-diarrhoeal activity and thus justifies its ethno-medicinal use in the treatment of diarrhoea.